Musical Composition "Kebyar Pitu" | Komposisi Musik "Kebyar Pitu" - I Gede Putu Bagus Yogi Waisnawa; I Ketut Muryana (GHURNITA: Jurnal Seni Karawitan, 2023)
The creation of a work of art, of course, has an idea that becomes the initial stimulus in the work, as well as in the musical art work "Kebyar Pitu" which starts from the stylist's personal experience of seeing a phenomenon so as to be able to make the stylist stimulated to use the phenomenon as an initial idea in creation. In this work, the idea that the stylist got from this phenomenon was to make a kekebyan percussion using the medium of expressing gamelan semarandana and having a structure in the form of Gineman, Gegenderan, Bapang and Pengcet. These four parts are the basis or framework in the musical art work "Kebyar Pitu". Besides that, there are also methods that help the stylist to realize the idea into a work, there are three methods that Alma M. Hawkins uses in the creation of this work, namely exploration, improvisation and forming. These three methods the stylist uses as a forum to describe creativity, effort and ideas that are able to create a new work such as the musical work "Kebyar Pitu".